An Analysis of the Control Environment and Whistleblowing Mechanisms on Fraudulent Practices by Village Government Officials in Bangka La’o, Manggarai Regency - Baso, Susana Purnamasari (Journal of Economics, Management and Accounting (JEMA), 2025)
This study was conducted at the Bangka La’o Village Office, Manggarai Regency, using primary and secondary qualitative data obtained through observation, interviews, and documentation. Data analysis followed the stages of collection, reduction, presentation, and conclusion drawing. The findings reveal that the control environment in Bangka La’o Village is highly unconducive, which has facilitated fraudulent practices by village officials. The seven indicators of the control environment are interrelated and contribute to the weakness of the oversight system. Furthermore, the presence of whistleblowers has proven effective in uncovering fraud cases, encouraging follow-up actions, and raising awareness among both village officials and the community in monitoring the village governance system. Based on these results, it is recommended that the village government strengthen internal control in accordance with the Ministry of Home Affairs Regulation No. 20 of 2018, enhance public awareness of whistleblowing, and establish a reporting system that ensures whistleblower protection in order to prevent future fraudulent practices.